Peran Guru Pendidikan Agama Islam dalam Mengembangkan Sikap Toleransi Siswa di SMAN 2 Sangatta Utara Kutai Timur - Maulidah, Imro’atuz Zuhroul; Mubarok, Ramdanil; Syafi'i, Muhammad Imam (Rabbani: Jurnal Pendidikan Agama Islam, 2024)
This research aims to analyze the role of Islamic religious education teachers in developing students' attitudes of tolerance, as well as the supporting and inhibiting factors faced by teachers in the process of developing students' attitudes of tolerance. This research uses a qualitative approach, and data collection techniques through observation, interviews and documentation. In contrast, the analysis technique uses Miles and Huberman analysis techniques with data condensation, data presentation, and verification. The results of this research show that PAI teachers at SMAN 2 Sangatta Utara play a role in developing students' attitudes of tolerance, PAI teachers act as educators, teachers, mentors, trainers and role models. Apart from that, PAI teachers also play a role in teaching the values ​​of tolerance through discussions, case studies and extracurricular activities, as well as creating an environment that respects diversity by encouraging positive interactions between students from various religious backgrounds. Supporting factors in implementing multicultural education include teacher commitment, cooperation with parents and the community, and support from the school administration while inhibiting factors include new students who have difficulty adapting and lack of support from the home environment, which is often internally related.